Bibliometric Analysis of Trends in Theory-related VUCA Publications - Nazaruddin Malik (Technium Social Sciences Journal, 2023)
This study aims to determine the results of the research development on Volatility, Uncertainty, Complexity and Ambiguity (VUCA) based on the Scopus database analysed in 2012-2022 with Bibliometric analysis with VOSViewer. The research theme Innovation and Leadership had the highest attention with a percentage of 16%.. Next showed that there were seven main themes that focused on four major themes: leadership, leaders, management, and environment, with the correlation and connectedness of the results of the Cluster Analysis based on the Coefficient value.